A jack of all trades: the multiple roles of the unique essential second messenger cyclic di‐AMP. Issue 2 (9th May 2015) - Commichau, Fabian M.; Dickmanns, Achim; Gundlach, Jan; Ficner, Ralf; Stülke, Jörg
Summary Second messengers are key components of many signal transduction pathways. In addition to cyclic AMP, ppGpp and cyclic di‐GMP, many bacteria use also cyclic di‐AMP as a second messenger. This molecule is synthesized by distinct classes of diadenylate cyclases and degraded by phosphodiesterases. The control of the intracellular c‐di‐AMP pool is very important since both a lack of this molecule and its accumulation can inhibit growth of the bacteria. In many firmicutes, c‐di‐AMP is essential, making it the only known essential second messenger. Cyclic di‐AMP is implicated in a variety of functions in the cell, including cell wall metabolism, potassium homeostasis, DNA repair and the control of gene expression. To understand the molecular mechanisms behind these functions, targets of c‐di‐AMP have been identified and characterized. Interestingly, c‐di‐AMP can bind both proteins and RNA molecules. Several proteins that interact with c‐di‐AMP are required to control the intracellular potassium concentration. In Bacillus subtilis, c‐di‐AMP also binds a riboswitch that controls the expression of a potassium transporter. Thus, c‐di‐AMP is the only known second messenger that controls a biological process by interacting with both a protein and the riboswitch that regulates its expression. Moreover, in Listeria monocytogenes c‐di‐AMP controls the activity of pyruvate carboxylase, an enzyme that is required to replenish the citric acid cycle. Here, we review the components of the c‐di‐AMP signaling system.